2009
DOI: 10.1007/bf03175142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical parameters, carbon and nitrogen sources on the production of alkaline protease from a newly isolatedBacillus pseudofirmus SVB1

Abstract: -The effect of process physical parameters (initial pH of the medium, temperature and rpm of the shaking incubator) on the production of alkaline protease from a newly isolated Bacillus pseudofirmus SVB1 was studied using central composite design technique. The individual optimum levels of initial pH of the medium, temperature and rpm of the shaking incubator were found to be 9.2, 27.3 °C and 195, respectively for the production of alkaline protease (specific activity, U/mg of protein) and 11, 28.9 °C and 210,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Several growth factors affect the productivity and growth of micro-organisms particularly substrate particle size is one of the most critical parameter [25]. It has been reported in lit-erature that low cost substrates like wheat flour, wheat bran, rice straws and molasses are suitably effective for growth and enzyme production [26,27]. Optimization of various environmental factors causes an increase of enzymatic activities [28].…”
Section: Production Of Cellulasementioning
confidence: 99%
“…Several growth factors affect the productivity and growth of micro-organisms particularly substrate particle size is one of the most critical parameter [25]. It has been reported in lit-erature that low cost substrates like wheat flour, wheat bran, rice straws and molasses are suitably effective for growth and enzyme production [26,27]. Optimization of various environmental factors causes an increase of enzymatic activities [28].…”
Section: Production Of Cellulasementioning
confidence: 99%
“…Several Bacillus strains such as Bacillus caldoproteolyticus [42], Bacillus clausii [43], Bacillus subtilis [44], Bacillus karajensis [45], Bacillus sp haericus [46], Bacillus pseudofirmus [47], Bacillus tequilensis [48] and Haloalkaliphilic bacterium sp [49] Moderate halophile Halomonas heilongjiangensis [50]. Borderline extreme halophile Halosiccatus urmianus [51].…”
Section: Enzymesmentioning
confidence: 99%
“…Particle size is considered to be the most critical factor among other growth factors, and greatly influenced the growth and enzyme yields of micro-organisms (Zadrazil and Puniya 1995). The previous literature illustrates that some low-cost agro-industrial substrates (molasses, rice straw, wheat bran, and flour) have a significant effect on production and maximally enhance enzyme yield (Mehta et al 2006;Sen et al 2009). Ojumu et al (2003) found that saw dust, corn cob, and bagasse agro substrates treated with 3% HCl increase cellulase activity at a maximum level.…”
Section: Production Of Endoglucanasementioning
confidence: 99%